Qualitative Indicators of Labour Standards Comparative Methods and Applications - Kucera, David (Social Indicators Research Series, 2007)
Recent years have witnessed a rapidly growing interest in the use and construction of "qualitative" indicators of labour standards. Qualitative indicators, while generally having numerical values, are based on such methods as grading by experts, the coding of legislation, and the coding of other textual sources addressing violations of a more de facto nature. Measuring compliance with labour standards is an undertaking intrinsically fraught with difficulty. For there are a number of possible sources of measurement error, both random and non-random, that are unique to such indicators, on top of those that affect qualitative and quantitative indicators alike. The growing use of qualitative indicators of labour standards thus raises a number of questions about comparative methods of construction as well as the appropriateness of particular methods for particular applications. This volume results from a seminar that was organized by the International Labour Office (ILO) to address these and related questions, bringing together experts from the ILO, universities and NGOs.